(untitled) (Ozone Therapy Global Journal, 2022)
SARS-CoV-2 is responsible for the outbreak of severe respiratory illness (COVID-19). Patients affected by COVID-19 during hospitalization may develop bedsores, in addition patients with previous ulcerative lesion have less chance of a successful evolution. These case report shown the evolution of two patients affected simultaneously by SARS-CoV-2 and lesions of various aetiology. One patient develop bedsore of about 14 cm in diameter in the sacral region during the hospitalization and other was affected by the Buruli ulcer. Both patients were treated locally using ozone bagging technique and local ozonized oil. The clinical evolution of the lesions was favourable after the first three applications, granulation tissue was evident during the first week and a total recovered was reached after 4-6 months. Ozone therapy may serve as complementary therapy in those conditions. The potential role of ozone therapy in this syndrome merits further research